Papillary thyroid carcinoma with Hashimoto’s thyroiditis: impact and correlation - Yao, Shengpeng; Zhang, Hong (Frontiers in Endocrinology, 2025)
Thyroid cancer is a malignant tumor of the endocrine system. Papillary thyroid carcinoma (PTC) is the most common form of thyroid cancer and has a comparatively better prognosis. An autoimmune disease called Hashimoto’s thyroiditis (HT) affects the thyroid and can cause lymphocyte infiltration in the thyroid tissue as well as hypothyroidism, which is characterized by increased levels of a certain antibody. It is currently assumed that there is a connection between PTC and HT. HT may increase the incidence of PTC and improve its prognosis by regulating gene expression, participating in common signaling pathways, and creating a specific immune microenvironment. In this review, we summarized the relationship between HT and PTC as well as the effects of coexisting HT on PTC and the possible mechanisms, thereby providing new perspectives for future research.